Uncertainties in the geographic context of health behaviors: a study of substance users' exposure to psychosocial stress using GPS data. Issue 6 (3rd June 2019) - Kwan, Mei-Po; Wang, Jue; Tyburski, Matthew; Epstein, David H.; Kowalczyk, William J.; Preston, Kenzie L.
ABSTRACT: This study examined how contextual areas defined and operationalized differently may lead to different exposure estimates. Substance users' exposures to environmental stress (in terms of two variables: community social economic status and crime) were assessed from global positioning systems (GPS) data. Participants were 47 outpatients with substance use disorders admitted for methadone maintenance at a research clinic in Baltimore, Maryland. From 35.2 million GPS tracking points, we compared 7 different methods for defining activity space. The different methods yielded different exposure estimates, which would lead to different conclusions in studies using only one method. These results have important implications for future research on the effect of contextual influences on health behaviors and outcomes: whether a study observes any significant influence of an environmental factor on health may depend on what contextual units are used to assess individual exposure.